Optimization of the Refining Process for a Fraction Rich in Crude Common Pony Fish (Leiognathus equulus) Oil as a By-product of Fish Protein Hydrolysate Processing Using The Response Surface Method - Rukmana, Jaka; Hariyadi, Purwiyatno; Hari Purnomo, Eko; Nur Faridah, Didah; Darniadi , Sandi (Politeknik Negeri Lampung., 2024)
The production of fish protein hydrolysate from common pony fish yields a fraction rich crude fish oil as a by-product. To utilize this by-product, refining is necessary to obtain common pony fish oil. This research aims to use a fraction rich crude fish oil from fish protein hydrolysate by-products to obtain fish oil and to determine the optimal conditions for the refining process using the response surface method (RSM) in the degumming, neutralization, and bleaching processes. The experimental design used was the Box–Behnken design, with the responses used to determine the optimum conditions at the degumming stage were water content and total dissolved solids. The response used to determine the optimum conditions at the neutralization stage was the refining factor, and at the bleaching stage was color (L, a*, b*). Parameters studied for each purification process include heating temperature (50-80°C), contact time between fraction rich crude fish oil with auxiliary materials (10-20 minutes) and the length of time for centrifugation (5-15 minutes) with a rotation speed of 10,062 G. The optimal conditions obtained in the degumming, neutralization, and bleaching processes for heating temperature, contact time between fraction rich crude fish oil with auxiliary materials, and centrifugation time, respectively, were 50°C, 10 min, 5 min; 50°C, 20 min, 5 min; and 80°C, 10 min, 15 min. Verification of the optimum conditions resulted in a free fatty acid value of 8.25% ± 0.01%, an acid value of 1.87 ± 0.02 mg KOH/g oil, a peroxide value of 1.04 ± 0.01 meq/Kg, an anisidine value of 11.11 ± 0.01 meq/Kg, a total oxidation value of 13.21 ± 0.01 meq/Kg and water content 6.052 ± 0.02 %. These results indicate a reduction in free fatty acids, acid number, peroxide number, anisidine number and water content by 66%, 90%, 73.5%, 61%, 63%, and 92% respectively. Our results showed that the purified fraction rich crude fish oil has met the SNI standards in parameter acid number, peroxide number, iodine number, anisidine number, and total oxidation value. The purification process that has been carried out can improve the quality fraction rich crude fish oil, but further processing still needs to be carried out to reduce water content and free fatty acid value